Observer-Cameramen as New Role in Educational Research: Case Study - Muchlas Abrori, Fadhlan (Universitas Pahlawan Tuanku Tambusai, 2025)
In educational research, observers and camera operators typically have distinct roles. However, these roles may not always function optimally in data collection due to certain limitations. As a result, the concept of merging the observer's role with the camera operators was introduced to address these challenges. This study explores the role of the idea in expanding the role of observers as cameramen (camera operators), which is presented in several cases conducted in North Kalimantan and East Java. The case studies in this research are based on three classroom settings with different observer characteristics regarding positioning, number, and role. This idea is also expanded through the discussion section in the paper, which presents an expansion of how to train observer-cameramen and maximize observers based on classroom size.